Answer:
S(x)= 10+2^x
Step-by-step explanation:
The correct function which represents the number of members in the science club after x weeks is,
S (x) = 10 + 2ˣ
We have,
The science club is experiencing a growth in membership.
On average, they are seeing 2 new members sign up each week.
Here, they started with 10 members.
Hence, The function S (x) which represents the number of members in the science club after x weeks is,
S (x) = 10 + 2ˣ
Where, x is number of weeks.
Therefore, The function is,
S (x) = 10 + 2ˣ
Learn more about the function visit:
https://brainly.com/question/11624077
#SPJ2
I will give you 10B points plus mark someone again for the Brainliest if you get this right.
Answer:
C
Step-by-step explanation:
Option c gives the actual representation of the question
Joey and Nolan are each solving the equation 13x - 42 = 18 - 7x. Joey's first step was to rewrite the equation as 20x - 42 = 18 while Nolan's first step was to rewrite the equation as 13x = 60 - 7x. Who is correctly applying the addition property of equality in the first step of his work? A. Only Joey B. Only Nolan C. Both Joey and Nolan D. Neither Joey nor Nolan
Answer:
Correct option: C.
(Both Joey and Nolan)
Step-by-step explanation:
The step Joey did is:
Add 7x to both sides of the equation
Then, he got:
13x - 42 + 7x = 18 - 7x + 7x
20x - 42 = 18
The step Nolan did is:
Add 42 to both sides of the equation
Then, he got:
13x - 42 + 42 = 18 - 7x + 42
13x = 60 - 7x
So both of them used correctly the addition property of equality in the first step of their work.
Correct option: C.
Find the missing factor
Answer:
The missing factor is (9s+1)
Step-by-step explanation:
The missing factor is (9s+1) because of the following
(9s^2 + s) + (18s+2)
If we factor out s from 9s^2+s, we get s(9s+1).
If we factor out 2 from 18s+2, we get 2(9s+1)
putting these together, we get s(9s+1) + 2(9s+1). Factoring out the common term of 9s+1, we get (9s+1)(s+2). therefore, the missing factor is 9s+1
What is the measure of < B, in degrees?
Answer:
B. 32°
Step-by-step explanation:
Since two of the sides are 10 in length, then we can infer that ∠A and ∠C are congruent. So, both equal 74°. You add 74 + 74 + x = 180, x would equal 32°.
Answer:
B
Step-by-step explanation:
sum of angle in triangle is 180
and since its isosceles triangle, it means <C will be same with <A
so we know that A + C = 148.
so the value of B will be like this
B = 180° - (A+C)° = 180 - 148 = 32°
Exactly 1 1/3 yard of ribbon is needed to make a bow. Which of the following lengths of ribbon could be used to make a bow with the least amount remaining?
The answer choice which could be used to make a bow with the least amount remaining is; 1 2/5 yards.
Which Length of ribbon renders the least remainder?It follows from the task content that the amount of ribbon remaining in each case can be evaluated as follows;
For 1 2/5 yards: 1 2/5 - 1 1/3 = 1/15. renders only 1/15 a yard to waste.
For 1 and 1/6 yards would render a waste of 1 1/6 yards since it is not possible to make a ribbon out of it.
1 2/10 yards would render a waste of 1 and 1/5 yards since it is not possible to make a ribbon out of it.
Read more on fractions;
https://brainly.com/question/78672
#SPJ1
An arithmetic sequence has this recursive formula. a1=9 and 1-3 .
The required explicit formula for the sequence is [tex]a_n = 9+(n+1)(-3)[/tex]. Option B is correct.
Given, an arithmetic sequance is given in the form of [tex]\left \{ {{a_1=9} \atop {a_n =a_{n-1}-3} \right.[/tex] .
Explicit formula for the sequence is to be determined.
Arithmetic progression is the sequence of numbers that have common differences between adjacent values.
Example, 1, 2, 3, 4, 5, 6. this sequence as n = 6 number with a = 1 (1st term) and common differene d = 2- 1 = 1.
Given arithmetic sequance is in the form of [tex]\left \{ {{a_1=9} \atop {a_n =a_{n-1}-3} \right.[/tex]
From above expression
[tex]a_n-a_{n-1}= -3[/tex]
common difference (d) = -3
with d = -3 and [tex]a_1 = 9[/tex]
The equation for the nth term in an arithmetic sequence is given by
[tex]a_n =a +(n-1)d[/tex]
[tex]a_n = 9 +(n-1)(-3)[/tex]
The above expression is the explicit form of the arithmetic equation.
Thus, the required explicit formula for the sequence is [tex]a_n = 9+(n+1)(-3)[/tex]. Option B is correct.
Learn more about arithmetic progression here:
https://brainly.com/question/20334860
#SPJ5
Is it possible to ride a bike 200 miles in 13 hours
Answer:
no
Step-by-step explanation:
because even going back to back it would take you about one or two days
Mehmut is 4 times as old as his brother, but
next year he will be only 3 times as old. Find
Mehmut's age now?
ALICIA CONYERS
7:20 AM
Answer:
Mehmut is 8 years old.
Step-by-step explanation:
From the statement we can get the following information, let M be Mehmut's age and b brother's age:
M = 4 * b
M + 1 = 3 * (b + 1)
We replace the first equation in the second and we are left with:
4 * b + 1 = 3 * b + 3
4 * b - 3 * b = 3 - 1
b = 2
Now, we replace to calculate M:
M = 4 * b
M = 4 * 2
M = 8
Mehmut is 8 years old.
Which graph represents an exponential function?
Answer:
The 1st Picture
Step-by-step explanation:
An exponential function is a base with an exponent of x. The parent graph f(x) will always have an asymptote at x= 0 and curve steeply.
Answer:
A
Step-by-step explanation:
took it a minute ago on edg
a family of 8 has 3 of them being males what proportion of the family is female
Answer: not very sure but i think that may be 5
Step-by-step explanation:
HELP ME PLEASE WILL MARK BRAINLIEST
Answer:
Bottom Left
Step-by-step explanation:
Break up the numbers to 7, and -8.
Break up the fractions to 1/5 and -3/5.
Solve for x: 3 < x + 3 < 6
Answer:
0 < x < 3
Step-by-step explanation:
3 < x + 3 < 6
Subtract 3 from all sides
3-3 < x + 3-3 < 6-3
0 < x < 3
Steps to solve:
3 < x + 3 < 6
~Subtract 3 to all sides
3 - 3 < x + 3 - 3 < 6 - 3
~Simplify
0 < x < 3
Best of Luck!
Explain the difference between perimeter and area. What do they measure? What types of units are they measured in? NEED ANSWER STAT!!!!!
Please help, I need this answer
Answer:
6.4
Step-by-step explanation:
By the Pythagorean Theorem:
[tex]c=\sqrt{5^2+4^2}= \\\\\sqrt{25+16}= \\\\\sqrt{41}\approx 6.4[/tex]
Hope this helps!
Answer:
To solve we need to use pythogorean theorm. So first we take the square of both giving us 25, 16. Then we add them and get 41. So the answer is squareroot of 41 and if you round you get 6.4
Answer: is approx. 6.4You are given the steps for constructing the bisector of an angle using a compass and a straightedge. Arrange the steps in the correct sequence
Step-by-step explanation:
position your compass at point A and using the same distance mark arcs on line AB(mark the point it meets the line D)and AC(mark the meeting point of the arc and the line E).Place your compass at D and draw an arc at the middle of the angle,using the same measurements position your compass at point E and draw an arc.Where the two arcs meet label F using a ruler draw a straight line from F to meet point A.
Note;the width of the compass when making the arcs should be the same always
is it a proportional relationship
Answer:
Yes
Step-by-step explanation:
The surface inside the circles will be painted green. The surface outside the circles will be painted white. What is the ratio of green paint to white paint you will need to paint these tiles? \((\pi^2-4):\pi^2\) a \(\pi^2:(\pi^2-4)\) b \(\pi:(4-\pi)\) c \((4-\pi):\pi\) d
Answer:
B, π:(4-π).
Step By Step:
With a side of length 12, we have an area of 144. The circle's radius is 3, so their area is 9π, per circle. All four circles have a total combined area of 36π - green. The area that is left of the square after the circles are painted green is 144-36π - White
So, the ratio of Green:White is (36π) : (144-36π), which simplifies to π:(4-π), B
Determining a Number of Solutions
Quick
Check
Determine whether the systems have one solution, no solution, or infinitely many solutions.
3x - 2y = 3; 6x - 4y = 1
One Solution
No Solution
Infinitely Many Solutions
3x - 5y = 8,5x - 3y = 2
3x + 2y = 8; 4x + 3y = 1
3x - y = 3; 2x - 4y = 2
3x - 4y = 2, 6x - y = 1
Intro
Done
Answer:
No Solution
Step-by-step explanation:
For one solution;
it will be consistent and independent ( example, x = 1 and y = 2)
For no solution;
it will be inconsistent and independent ( example, 0 = 2)
For many solution;
it will be consistent and dependent ( example, 1 = 1, 2 = 2, y = y, x = x)
Given;
3x - 2y = 3 -------------- equation (1)
6x - 4y = 1 --------------- equation (2)
6: 18x - 12y = 18 -------------equation (3)
3: 18x - 12y = 3 --------------- equation (4), subtract (4) from (3)
--------------------------------------------
0 - 0 = 15
-----------------------------------------------
0 = 15
The solution is inconsistent and independent, because zero (0) cannot be equal to 15
Thus, the system has no solution
Answer:
ONE SOLUTION
3x-5y=8; 5x-3y=2
3x+2y=8; 4x+3y=1
NO SOLUTION
3x-4y=2; 6x-8y=1
3x-2y=3; 6x-4y=1
INFINITELY MANY SOLUTIONS
3x-6y=3; 2x-4y=2
Step-by-step explanation:
i got this right on edge
If A(4 -6) B(3 -2) and C (5 2) are the vertices of a triangle ABC fine the length of the median AD from A to BC. Also verify that area of triangle ABD = Area of triangle ACD
Answer:
a) The median AD from A to BC has a length of 6.
b) Areas of triangles ABD and ACD are the same.
Step-by-step explanation:
a) A median is a line that begin in a vertix and end at a midpoint of a side opposite to vertix. As first step the location of the point is determined:
[tex]D (x,y) = \left(\frac{x_{B}+x_{C}}{2},\frac{y_{B}+y_{C}}{2} \right)[/tex]
[tex]D(x,y) = \left(\frac{3 + 5}{2},\frac{-2 + 2}{2} \right)[/tex]
[tex]D(x,y) = (4,0)[/tex]
The length of the median AD is calculated by the Pythagorean Theorem:
[tex]AD = \sqrt{(x_{D}-x_{A})^{2}+ (y_{D}-y_{A})^{2}}[/tex]
[tex]AD = \sqrt{(4-4)^{2}+[0-(-6)]^{2}}[/tex]
[tex]AD = 6[/tex]
The median AD from A to BC has a length of 6.
b) In order to compare both areas, all lengths must be found with the help of Pythagorean Theorem:
[tex]AB = \sqrt{(x_{B}-x_{A})^{2}+ (y_{B}-y_{A})^{2}}[/tex]
[tex]AB = \sqrt{(3-4)^{2}+[-2-(-6)]^{2}}[/tex]
[tex]AB \approx 4.123[/tex]
[tex]AC = \sqrt{(x_{C}-x_{A})^{2}+ (y_{C}-y_{A})^{2}}[/tex]
[tex]AC = \sqrt{(5-4)^{2}+[2-(-6)]^{2}}[/tex]
[tex]AC \approx 4.123[/tex]
[tex]BC = \sqrt{(x_{C}-x_{B})^{2}+ (y_{C}-y_{B})^{2}}[/tex]
[tex]BC = \sqrt{(5-3)^{2}+[2-(-2)]^{2}}[/tex]
[tex]BC \approx 4.472[/tex]
[tex]BD = CD = \frac{1}{2}\cdot BC[/tex] (by the definition of median)
[tex]BD = CD = \frac{1}{2} \cdot (4.472)[/tex]
[tex]BD = CD = 2.236[/tex]
[tex]AD = 6[/tex]
The area of any triangle can be calculated in terms of their side length. Now, equations to determine the areas of triangles ABD and ACD are described below:
[tex]A_{ABD} = \sqrt{s_{ABD}\cdot (s_{ABD}-AB)\cdot (s_{ABD}-BD)\cdot (s_{ABD}-AD)}[/tex], where [tex]s_{ABD} = \frac{AB+BD+AD}{2}[/tex]
[tex]A_{ACD} = \sqrt{s_{ACD}\cdot (s_{ACD}-AC)\cdot (s_{ACD}-CD)\cdot (s_{ACD}-AD)}[/tex], where [tex]s_{ACD} = \frac{AC+CD+AD}{2}[/tex]
Finally,
[tex]s_{ABD} = \frac{4.123+2.236+6}{2}[/tex]
[tex]s_{ABD} = 6.180[/tex]
[tex]A_{ABD} = \sqrt{(6.180)\cdot (6.180-4.123)\cdot (6.180-2.236)\cdot (6.180-6)}[/tex]
[tex]A_{ABD} \approx 3.004[/tex]
[tex]s_{ACD} = \frac{4.123+2.236+6}{2}[/tex]
[tex]s_{ACD} = 6.180[/tex]
[tex]A_{ACD} = \sqrt{(6.180)\cdot (6.180-4.123)\cdot (6.180-2.236)\cdot (6.180-6)}[/tex]
[tex]A_{ACD} \approx 3.004[/tex]
Therefore, areas of triangles ABD and ACD are the same.
and the Aegean Sea is located at
On the map above, the Black Sea is located at
A Letter A Letter C
B. Letter C Letter B
C Letter A Letter B
D. Letter B Letter A
Answer:
The answer to your question is C.
Step-by-step explanation:
Have a nice day :)
M is less than angleAOC = 108 degrees m is less than angle AOB = 3x + 4 degrees m is less than angle BOC = 8x - 28 degrees Find m is less than angle AOB
Answer: angleAOB = 40°
Step-by-step explanation: Drawing these angles, we see that angle AOC is the sum of angle AOB and angle BOC, so:
angleAOC = angleAOB + angleBOC
108 = 3x + 4 + 8x - 28
108 + 24 = 11x
11x = 132
x = 12
Knowing x, to find angleAOB, just substitute and calculate:
angleAOB = 3x+4
angleAOB = 3.12 + 4
angleAOB = 40°
The angle AOB is 40°.
Determine the constant of variation for the direct variation given.
2
1
1/2
Answer:
1/2
Step-by-step explanation:
The constant of variation is the same as the slope. From the graph, the slope is 1/2.
Answer:
I believe the answer is 2
Multiply.
11 x 2 =
Submit
Is it 22
Answer:
yes
Step-by-step explanation:
Answer:
Yes...yes it is.
Step-by-step explanation:
Another way to help you see it is as adding 11 + 11, because the equation is stating that there are two 11's.
y+7=-2(x+3)
intercept form ):
Answer:
y = -2x - 13
Step-by-step explanation:
Answer:
y = - 2x - 13
Step-by-step explanation:
First, distribute out the two on the right side of the equation.
y + 7 = - 2x - 6
Next, subtract 7 from both sides to isolate the y variable on the left side.
y = - 2x - 13
That is your answer in slop-intercept form.
simplify √x^2+6x+9 if x≥3
Answer:
simplified expression for √x^2+6x+9 if x≥3
is x+3
Step-by-step explanation:
[tex]\sqrt{x^2+6x+9} \\=>\sqrt{x^2+3x+3x+9} \\=>\sqrt{x(x+3)+3(x+3)} \\=>\sqrt{(x+3)(x+3)} \\=>\sqrt{(x+3)^2}\\=>(x+3) \ or -(x+3)[/tex]
but given that x≥3
then we have to negate solution -(x+3)\
Then simplified expression for √x^2+6x+9 if x≥3
is x+3
Language is a complex system that includes the ways we express ourselves, such as speaking or writing, and ways we receive information, such as listening and reading. a. true b. false
Answer: False, language is a more specific word.
Step-by-step explanation:
Language is a complex and structured system of communication.
This word particularly refers to the "artificial codes or ciphers" that humans use to communicate.
The thing in the sentence is more general than language, this refers to communication:
"Communication is a complex system that includes the ways we express ourselves, such as speaking or writing, and ways we receive information, such as listening and reading."
So the actual sentence is false.
What is the image of (-1, 1) after a dilation of 2?
O (1.3)
O (2.2)
O (-22)
Answer:
(-2, 2)
Step-by-step explanation:
When an image is dilated by a factor of 2, we can simply multiply the x and y coordinates by 2.
Therefore, the coordinates will become (-2, 2).
The maximum point on the graph of the equation
y = f(x) is (2,-3). What is the maximum point on
the graph of the equation y=f(x-4)?
Answer:
(6, - 3 )
Step-by-step explanation:
Given f(x) then f( x + c) represents a horizontal translation of f(x)
• If c > 0 then a shift to the left of c units
• If c < 0 then a shift to the right of c units, thus
y = f(x - 4) represents a shift to the right of 4 units, so
(2, - 3 ) → (2 + 4, - 3 ) → (6, - 3 )
The maximum point on the graph after translation y = f( x -4) is (6 , -3)
What is translation of a graph?Translation of a graph is the movement of the graph either in horizontal direction or vertical direction .
Horizontal translation to the left is given by f (x+ c) ,c >0
: (x, y) → (x- c , y)
Horizontal translation to the right is given by f (x- c) ,c >0
: (x, y) → (x+ c , y)
Given that the maximum point on the graph of the equation
y = f(x) is (2,-3)
To find the maximum point on the graph of the equation y = f(x-4)
f(x -4) is Horizontal Translation to the right with 4 units , c= 4
then (x, y) → (x+ c , y)
Thus the maximum point (2,-3) is moved to ( 2 +c , -3)
⇒ (2+ c , -3) = (2+4 , -3) = ( 6 , -3)
Therefore, the maximum point of the graph of the equation y = f(x-4) becomes (6,-3)
Also, Learn more abut translation of graphs from the link below:
https://brainly.com/question/11805053
#SPJ5
find the area of a rectangle with a width of 16 centimeters and a length of 55 centimeters
Answer:
The area of the rectangle is 880 cm
Step-by-step explanation:
Lenght = 55cm
Breadth/width=16cm
Area of rectangle= lenght×breadth
Area= 55×16
Area= 880
Hence, area of rectangle is 880cm
P.S - Mark me as the brainliest :D